ПИТАНИЕ И УПИТАННОСТЬ ЩУКИ ESOXLUCIUS L., 1758 В ВОДОХРАНИЛИЩАХ КАНАЛА ИМ. К. САТПАЕВА (Eurasian Journal of Ecology, 2016)
Actual materials on a feeding and state of nourishment of a pike (Esox lucius L., 1758) in reservoirs of the K. Satpaev's channel are resulted. The variability of feeding parameters into population of this species from investigated reservoirs is discussed. Age dependence of decrease in intensity of a feeding is marked. At comparison chronological groups from 2000 - 2012 years on distinctions of feeding intensity not revealed. As the basic objects of a pike feeding in channel reservoirs serve roach (Rutilus rutilus (L., 1758)) and perch (Perca fluviatilis L., 1758), in reservoir № 11 - goldfish (C. auratus (L., 1758)). The conclusions about satisfactory character of a food of a pike in reservoirs, and as about necessity of strengthening of a catching press on this species and its feeding object's populations become.